2015
DOI: 10.1128/aem.03092-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Physiological Insights into the Robustness of Long Filamentous Cells of Methanosaeta harundinacea, Prevalent in Upflow Anaerobic Sludge Blanket Granules

Abstract: bMethanosaeta spp. are widely distributed in natural environments, and their filamentous cells contribute significantly to sludge granulation and the good performance of anaerobic reactors. A previous study indicated that Methanosaeta harundinacea 6Ac displays a quorum sensing-regulated morphological transition from short to long filaments, and more acetate is channeled into methane production in long filaments, whereas more is channeled into biomass synthesis in short filaments. Here, we performed transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The role of H2 as electron mediator in MES systems has been extensively discussed (Blanchet et al, 2015;Jourdin et al, 2016b;LaBelle and May, 2017;Puig et al, 2017) and some biofilms were showed to be very effective at capturing it before it could escape the biofilm (Jourdin et al, 2016b). Some methanogens belonging to genera such as Methanosaeta and Methanospirillum were also showed to form long filaments over hundreds of micrometers in anaerobic granular sludge (Parshina et al, 2014;Li et al, 2015;Zhou et al, 2015). However, methanogenesis activity was inhibited in our reactors by continuously feeding a chemical inhibitor.…”
Section: High Microorganism Morphology Diversity With Filamentous Micmentioning
confidence: 79%
“…The role of H2 as electron mediator in MES systems has been extensively discussed (Blanchet et al, 2015;Jourdin et al, 2016b;LaBelle and May, 2017;Puig et al, 2017) and some biofilms were showed to be very effective at capturing it before it could escape the biofilm (Jourdin et al, 2016b). Some methanogens belonging to genera such as Methanosaeta and Methanospirillum were also showed to form long filaments over hundreds of micrometers in anaerobic granular sludge (Parshina et al, 2014;Li et al, 2015;Zhou et al, 2015). However, methanogenesis activity was inhibited in our reactors by continuously feeding a chemical inhibitor.…”
Section: High Microorganism Morphology Diversity With Filamentous Micmentioning
confidence: 79%
“…Different factors in Methanosaeta , which can be considered a key player in granule formation (Quarmby and Forster, ; Hulshoff Pol et al ., ), seem to be regulated by quorum sensing signalling molecules (Zhang et al ., ; Li et al ., ). This mainly includes the filamentous morphology of Methanosaeta (Zhang et al ., ; Zhou et al ., ), necessary to engage in granule formation. Quorum sensing also plays an important role in structural sludge formation with respect to biofouling, which affects membrane bioreactor systems in general, and anaerobic membrane reactors in particular (Yeon et al ., ; Jiang et al ., ).…”
Section: Microbial Communication In Admentioning
confidence: 99%
“…A misinterpretation may arise, because only recently a rodlike Methanosaeta harundinacea was described [55]. It seems that the rod-like form of M. harundinaceae represents a very active culture in a high division mode [55].…”
mentioning
confidence: 99%